Pendekatan Konsep Penerapan Green Infrastructure Pada Kawasan Perumahan Berbasis Komunal - Muliani, Fitri; Miswar, Khairul; Munandar, Aris; Rinaldy, Deri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Almuslim, 2024)
This research aims to discuss policies and implementation of green infrastructure in Indonesia in communal-based housing areas. The references used for come from problems and best practices from other countries that have implemented green infrastructure. The method used is a descriptive method with a literature review approach. This research was carried out by understanding concepts, regulations, application of concepts, as well as identifying problems and providing recommendations related to green infrastructure in Indonesia. Based on the research results, there are six main regulations that serve as a reference for implementing green infrastructure in residential areas in Indonesia. Where the important thing in this regulation is Green Open Space (RTH) in the city with a minimum area proportion of 30%, rainwater storage is also set at a capacity of 50% of the amount of rainwater that falls according to annual rainfall and a general room temperature of 25 degrees Celsius. with relative humidity of 60%. The main problem is that 30% to 40% of carbon dioxide emissions are produced by buildings, which shows that buildings have a significant contribution to the process of environmental damage, as do residential areas. In Indonesia, the concept of green infrastructure that is applied is oriented towards zero energy use and the use of renewable energy. Holistic policy regulations are needed, from upstream to downstream as a form of implementing green infrastructure in residential areas, such as several developed countries in the world, namely the United States, England and Singapore, which have implemented policy regulations for sustainable implementation of green infrastructure in their countries.